2005
DOI: 10.3748/wjg.v11.i5.712
|View full text |Cite
|
Sign up to set email alerts
|

Existence and significance of hepatitis B virus DNA in kidneys of IgA nephropathy

Abstract: HBV infection might play an important role in occurrence and progress of IgAN. In addition to humoral immune damages mediated by HBAg-HBAb immune complex, renal tissues of some IgAN are directly infected with HBV and express HBAg in situ, and the cellular mechanism mediated by HBV originating from renal cells in situ may also be involved in the pathogenesis of IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Beaufils et al [12] undertook a systematic study of kidney in deceased AIDS patients using light and immunofluorescence microscopy and found that 7.75% showed diffuse mesangial IgA deposits. Wang et al [13] detected hepatitis B virus antigens by immunohistochemistry in renal tissues in 50 cases of IgAN; it was amazing to find that the positive rate of HBAg, HBsAg, and HBcAg was 82, 58 and 42% in glomeruli, respectively. However, the cellular mechanism mediated by virusin situ, which involved in the pathogenesis of IgAN, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Beaufils et al [12] undertook a systematic study of kidney in deceased AIDS patients using light and immunofluorescence microscopy and found that 7.75% showed diffuse mesangial IgA deposits. Wang et al [13] detected hepatitis B virus antigens by immunohistochemistry in renal tissues in 50 cases of IgAN; it was amazing to find that the positive rate of HBAg, HBsAg, and HBcAg was 82, 58 and 42% in glomeruli, respectively. However, the cellular mechanism mediated by virusin situ, which involved in the pathogenesis of IgAN, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…3 The association of membranous nephropathy (MN) with HBs antigenemia has been well established in endemic regions, 4 although the etiological role of hepatitis B virus (HBV) antigenemia and HBV antigen deposition in IgAN remains speculative. 5,6 Researchers who suggest a strong association between IgAN and HBs antigenemia indicate that mesangial and subendothelial trapping of circulating immune complexes and subendothelial deposits results in the onset of IgA nephropathy with hepatitis B surface antigen (HBs-IgAN). [7][8][9] In case of HBV-associated membranous nephropathy (HBV-MN), unlike the prognosis in affected children, that in adults is not favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cellular mechanism mediated by HBV originating from renal cells in situ might also be involved in the pathogenesis of IgAN. 10 In a retrospective study, Lai and coworkers reported 21 patients with hepatitis B surface antigenemia and IgAN; clinical presentations included macroscopic hematuria in four patients (19%), nephrotic syndrome in four patients (19%), microscopic hematuria in five patients (24%), asymptomatic proteinuria and hematuria in three patients (14%), and chronic kidney disease in one patient (5%); 19% of these patients developed progressive renal failure over a mean follow-up period of 40 months. 13 The role of HBV in the pathogenesis of different types of glomerulonephritis has yet to be clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that HBV infection might play an important role in both occurrence and progression of IgAN. [10][11][12] Wang et al 10 have shown that in addition to the humoral immune-mediated damage by HBV antigen-antibody immune complex, the renal tissues of some IgAN cases are directly infected with HBV and express HBV antigens in situ. Thus, cellular mechanism mediated by HBV originating from renal cells in situ might also be involved in the pathogenesis of IgAN.…”
Section: Discussionmentioning
confidence: 99%